2014
DOI: 10.1590/s0100-204x2014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de vacas de corte Purunã submetidas a diferentes manejos de amamentação

Abstract: Resumo -O objetivo deste trabalho foi avaliar o desempenho ponderal e reprodutivo de vacas de corte submetidas a diferentes manejos de amamentação. Durante a estação de monta, de 85 dias, foram avaliadas 161 vacas de corte da raça Purunã, de acordo com os seguintes manejos de amamentação: desmame precoce, vacas separadas dos seus bezerros aos 75 dias pós-parto; amamentação controlada, vacas separadas de seus bezerros aos 75 dias de idade, mas colocadas para amamentar uma vez ao dia durante a estação de monta; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
1
5
0
1
Order By: Relevance
“…The larger proportion of kilograms of calf in relation to the cow weight both at calving and at weaning are indicative of efficiency, as they demonstrate production as a function of the cost of maintenance of the females, which is the highest production cost. These efficiencies can be influenced by the time of birth of the calves and cow age (Bocchi, Teixeira, & Albuquerque, 2004), cow genetic group and calf sex (Ribeiro et al, 2001), nutritional level pre-and postpartum (Ribeiro et al, 2001;Vaz et al, 2016), and calf age at weaning (Moura et al, 2014;Vaz et al, 2010). The present findings are corroborated by the literature, where the cow body size did not lead to increased calf weights relative to the cow weight (Vaz et al, 2016), these two variables being actually proportional to the size of the dam.…”
Section: Resultssupporting
confidence: 88%
“…The larger proportion of kilograms of calf in relation to the cow weight both at calving and at weaning are indicative of efficiency, as they demonstrate production as a function of the cost of maintenance of the females, which is the highest production cost. These efficiencies can be influenced by the time of birth of the calves and cow age (Bocchi, Teixeira, & Albuquerque, 2004), cow genetic group and calf sex (Ribeiro et al, 2001), nutritional level pre-and postpartum (Ribeiro et al, 2001;Vaz et al, 2016), and calf age at weaning (Moura et al, 2014;Vaz et al, 2010). The present findings are corroborated by the literature, where the cow body size did not lead to increased calf weights relative to the cow weight (Vaz et al, 2016), these two variables being actually proportional to the size of the dam.…”
Section: Resultssupporting
confidence: 88%
“…A complementary analysis demonstrated that the PP at the end of the PD was higher in heavier cows at calving and with higher levels of P4 at 30 dPP, especially in W180 cows. Studies showed that the highest PP was observed in cows with greater body condition at calving and a low rate of pregnancy loss, emphasizing the importance of ensuring good nutritional status in the pre‐calving period to achieve BCS greater than 3.0 (Ayres et al, 2014; Moura et al, 2014) and to anticipate the return to postpartum cyclic activity (Joner et al, 2018). However, there was no difference in BW at birth between treatments, although W180 cows had a relatively lower BW that may have influenced this result.…”
Section: Discussionmentioning
confidence: 99%
“…El desempeño reproductivo de bovinos para carne en el trópico es afectado por factores ambientales, generalmente asociados con la condición corporal al parto y su dinámica durante el periodo posparto (1) . El intervalo entre el parto y el reinicio de la actividad ovárica puede ser un obstáculo importante para la mejora de la eficiencia reproductiva, ya que es el principal responsable del aumento del intervalo entre partos (2) , que es influenciado por la raza, nutrición, producción de leche, presencia del becerro, estación del año, presencia del semental (3) y el número de parto (4) .…”
unclassified
“…Otra medida para valorar la eficiencia reproductiva del ganado bovino son los días abiertos, además, la obtención de información requiere menos tiempo; por tal motivo, su uso se justifica en la selección para mejorar el comportamiento reproductivo (8) . Dado que los Reproductive performance of beef cattle in the tropics is affected by environmental factors usually associated with body condition at calving and their dynamics during the postpartum period (1) . The interval between calving and the resumption of ovarian activity can be a major obstacle to the improvement of the reproductive efficiency, as it is responsible for the calving interval (2) , which is influenced by breed, nutrition, milk production, presence of the calf, season of the year, presence of the sire (3) and number of calving (4) .…”
mentioning
confidence: 99%